ANALYSIS OF OPERATIONAL RISKS IN THE STORAGE OF LIQUID AMMONIUM NITRATE IN A PETROCHEMICAL PLANT, THROUGH THE HAZOP METHODOLOGY (2023)
The storage of liquid ammonium nitrate in a petrochemical plant, located at the Caribbean region of Colombia, is analyzed to identify and mitigate the risks present in it. Hazard and Operability (HAZOP) methodology was followed to assess the risks and hazards associated to this process. Initially, the ammonium nitrate storage tank was defined as the node to be studied, together with the instrumentation required for this operation. The diagrams of the node and technical specifications of the equipment and instruments were reviewed. This information, together with the operative, technical and conceptual knowledge of the staff at the plant, allowed to assess the deviations for operational variables such as temperature, pressure and level, among others, in order to identify the hazards and risk scenarios that can take place during the storage of ammonium nitrate. Based on the HAZOP analysis, recommendations were made to mitigate or avoid incidents that have an impact on people, environment or the company. This case study highlights the qualitative deviations and variables that require a constant monitoring and control for a safe storage of ammonium nitrate. Copyright © 2018, AIDIC Servizi S.r.l.